(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article explores how Artificial Intelligence (AI) is changing the way learners acquire and practice languages, asking whether “smart tools” automatically make “smart learners.” It examines how AI-based language apps, chatbots, and writing assistants affect learners’ autonomy, motivation, and critical thinking. Drawing on recent research, the article argues that AI can enhance language learning only when learners are taught to use it strategically and critically. The discussion highlights benefits such as increased practice and feedback, as well as risks such as over-reliance, passivity, and shallow engagement. The article concludes with practical principles for turning AI tools into instruments of learner empowerment rather than dependence.